FAKTOR RISIKO CORONAVIRUS ANXIETY PADA PETUGAS LOKET PT. POS INDONESIA KANTOR CABANG UTAMA JAKARTA PREMIER TAHUN 2022 - Irfan Rida Putra (2022)
Coronavirus Anxiety is the anxiety experienced by individuals during the COVID19 pandemic. Postal Office Clerk is one of the jobs at risk of experiencing Coronavirus Anxiety seen from the intensity of contact with other people, money, and also goods that have the potential to be a medium of transmission of Covid-19. This study aimed to determine the risk factors that could affect Coronavirus Anxiety at the PT. Pos Indonesia. This study uses a cross-sectional design carried out at PT. Pos Indonesia Main Branch Office Jakarta Premier in June 2022. The population of this research is the counter staff of PT. Pos Indonesia Main Branch Office Jakarta Premier. The sample used was 50 respondents taken using a total sampling technique. Research data were collected through primary data. Primary data were taken through the Coronavirus Anxiety Scale questionnaire, respondent characteristics questionnaire, perception in application of health protocols in the workplace, and perception in adherence to health protocols in the workplace. Based on the results of the bivariate analysis, the factors that areassociated to Coronavirus Anxiety were the age of the respondent (p value = 0.023; POR = 4,571); educational level (p-value = 0.020; POR = 5,091); History of Covid-19 infection (p-value = 0.003; POR = 9,333);Perception in Implementation of health protocols in the workplace (p-value = 0.009; POR = 6,000); and perception in adherence to the application of health protocols (p-value = 0.004; POR = 7,111). Companies can continue to improve the quality of health protocols and control of their implementation, and immediately createdevelop programs to overcome Coronavirus Anxiety in their workers. Keywords: Anxiety, COVID-19, Compliance, Health Protocol, Vaccines